The Role of Patronage in early nineteenth-century science, as evidenced in letters from Humphry Davy to Joseph Banks. (1st May 2019) - Fulford, Tim
Abstract : The recently published Collected edition of Davy's letters throws new light on the importance and modus operandi of Banksian patronage as a means of organizing and promoting science. It demonstrates how dependent on, and manipulative of, Banks's favour Davy's careerism was, despite his later fame as an original genius. Here, I select from the edition some examples that offer new perspectives on how the patronage relationship worked—how Davy fashioned himself to be patronized, as well as how Banks operated as patron. Discussing Davy's activities at the Royal Institution, at the Royal Society and for the Board of Agriculture, I show that his public success allowed him to shift the power balance in this relationship, so that he was able to call upon Banks's support over issues of his choice, and, during the safety lamp affair (1815–18), to cause Banks to take the rare step of entering a scientific controversy in the newspapers. This shift to a highly public medium heralded a significant change: in a new era of widespread industrialization, in which engineers operating outside scientific institutions had increasing scope to put their inventions into production, priority—and the general reputation of scientific knowledge—increasingly needed demonstration before a wider court of public opinion than hitherto. Davy pulled Banks into a new, exposed, position in an expanded and oppositional public sphere. After Banks died, and Davy was no longer a protégé of a powerful patron but was himself in a position to distribute patronage—Banks's successor as President of the Royal Society and Commissioner of the Board of Longitude—the letters reveal the strengths and limitations of Banksian governance in an era in which science was specializing and was increasingly discussed in the national press. Davy rejected some of his predecessor's policies but essentially retained Banks's method of directing science by privately exerting influence and controlling patronage. I suggest that this method was relatively successful at the Royal Society, where Davy managed (uneasily) to incorporate a generation of mathematical savants excluded by Banks; at the Board of Longitude it failed: Davy's efforts to emulate Banks as the promoter of exploration fell foul of institutional intransigence that he had neither power nor influence enough to shift.